2006 IEEE International Technology Management Conference (ICE) 2006
DOI: 10.1109/ice.2006.7477092
|View full text |Cite
|
Sign up to set email alerts
|

What ontologies for PLM: A critical analysis

Abstract: Product development environments are known for their growing complexity, especially if they are envisioned for the whole product Iifecycle. The objective of the PLM business activity is to manage products across their Iifecycles, from cradle to grave. PLM is focused on the product, and holistically brings together many product-related components. For such environments, ontologies could play an important role to ensure semantic interoperability and correct information exchange. But what kinds of ontologies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Enquiry on existent works [14] about ontologies and formal approaches [6,12,13,16] [7,8] are covering only partially our needs. They are upper level ontologies with insuficient granular precision required to describe resources in our use case.…”
Section: Methodsmentioning
confidence: 99%
“…Enquiry on existent works [14] about ontologies and formal approaches [6,12,13,16] [7,8] are covering only partially our needs. They are upper level ontologies with insuficient granular precision required to describe resources in our use case.…”
Section: Methodsmentioning
confidence: 99%
“…maintenance statistics. Ontologies have been considered as basis for PLM models (Mostefai & Bouras 2006) (Borsato u. a. 2010).…”
Section: Complexity In Product Modelsmentioning
confidence: 99%
“…Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model. In that sense, the heavyweight ontology dimension of this work builds on top of the current perceived advantages of applying formal ontologies within a PLM context to aid the process of semantic interoperability and knowledge exchanges [3,6,7,16,17].…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
“…The contribution by Kesavadas et al [28] acknowledges the use of formal ontologies to progressively capture design and manufacturing concepts. Other authors [17,29,30] have identified the potentials of using upper level and core ontologies from which to relate PLM structures. Unfortunately, these approaches either still lack the level of semantic rigour or need to be further explored in order to be industrially viable.…”
Section: Combined Plm and Knowledge-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation